2016
DOI: 10.1021/acscatal.6b01759
|View full text |Cite
|
Sign up to set email alerts
|

AuNP–Polymeric Ionic Liquid Composite Multicatalytic Nanoreactors for One-Pot Cascade Reactions

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 69 publications
0
28
0
Order By: Relevance
“…2). 91 The structural analysis revealed that appropriately controlling the self-assembly and self-organization of the constitutive building blocks during their synthesis can optimize the microenvironments for each reaction, determining the diffusion of the intermediates from the shell to the core and out from the core to the reaction media.…”
Section: Pil-metal Nanoparticle Compositesmentioning
confidence: 99%
“…2). 91 The structural analysis revealed that appropriately controlling the self-assembly and self-organization of the constitutive building blocks during their synthesis can optimize the microenvironments for each reaction, determining the diffusion of the intermediates from the shell to the core and out from the core to the reaction media.…”
Section: Pil-metal Nanoparticle Compositesmentioning
confidence: 99%
“…To the best of our knowledge, there are only two reports about the reduction of α‐cyano‐α,β‐unsaturated esters …”
Section: Resultsmentioning
confidence: 99%
“…In other reports, Luis et.al reported two‐step Knoevenagel reaction‐reduction over a bifunctional catalyst containing Au nanoparticles . They could reduce the alkane, ester and nitro groups to alkane, alcohol and amine groups at 24 hr using 20 mmol NaBH 4 .…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of the Ru@PsIL catalyst was performed by modifying the reported procedure (Figure S2 in the Supporting Information) . Typically, the Ru@PsIL was synthesized by the immobilization of Merrifield peptide resin with 1,2‐dimethyl‐1 H ‐imidazole to give PsIL (Scheme S2 in the Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…The presence of functional moieties with ionic nature in the polymer backbone enhances the dispersion and stabilization of NPs. Also, the immobilized ILs as supports for catalysts, not only benefit from the excellent physicochemical properties of ILs but also help in increasing the recyclability of catalysts and ease catalyst–product separation . The immobilization of ILs on polymers lets them act as a solid support and provide a similar electronic environment as ILs for the stabilization of NPs…”
Section: Introductionmentioning
confidence: 99%